External causes in women assisted by the Mobile Emergency Service - SAMU, in Espírito Santo, Brazil. (30th September 2020) - Machado, E; Almeida, F; Neto, C; Barbosa, R; Sogame, L; Oliveira, J; Pinto, H; Duarte, S; Vieira, L
Abstract: Background: External causes are events that lead to traumas, injuries and any health problems, whether deliberate or not, with sudden onset and with immediate consequence, which may or may not lead to death or incapacitating injuries. Studies show that the main causes of death of women in fertile period are external causes, and they associate this fact with the change in habits and lifestyle adopted by this group in modern times that make them more vulnerable to the risks of becoming ill or dying from such causes. The objective of this study is precisely to analyze the prevalence of the main external causes in women assisted by SAMU 192 in Espírito Santo, Brazil, and in this way, assist in the development of accident and violence prevention strategies and also contribute to the scientific society through the description of the profile epidemiological profile of these events. Methods: This is a cross-sectional study of primary care provided by SAMU 192, in the state of Espírito Santo, in 2015, in which only women victims of traffic accidents, aggression or falls were selected. Results: Among the women assisted by SAMU 192, 23.5% were victims of accidents and violence. Of this total, 48.6% received assistance for falls, 46.6% for traffic accidents and 4.9% for aggression. Adulthood was the most frequent, with an average age of 44.9 ± 22.7 years. Conclusions: External causes involving women represent a major problem in Brazil and worldwide. In Espírito Santo, falling was the most common type of external cause and mainly affected the elderly woman, while the traffic accident mainly affected the adult woman. As for the aggressions, these occurred mainly at night with association with the use of alcoholic beverages. Thus, it is immensely necessary to develop actions to promote and prevent external causes of harm to women's health in the state of Espírito Santo. Key messages: Knowing what affects the most women's health in an emerging country like Brazil, is essential for public policy actions aimed at reducing the femininity, sexism and the death of women in general. Violence against women is an underreported event because of several factors, leading to the concealment of violence, emphasizing once again the importance of public policies for this purpose.